Relationship between Employment Stress, Household Income, and Social and Health-risk Behaviors in Students with International Experiences (Undergraduate Research Journal; 2017, 2017)
While numerous researches portray positive relationship between stress and health-risk behaviors, such as smoking and drinking, some studies claimed that other third variables predicted increased health-risk behaviors instead. Furthermore, researches seemed to yield different results according to countries and/or races too. In a research, Blacks and Hispanics were found to be more likely to experience higher levels of stress than Whites do but were also found be more resilient to stress due to various support systems (Krueger, Saint Onge, & Chang, 2011). In addition, in South Korea, notorious for high suicide rates and stress levels, there have been several studies on a concept of employment stress, or job-seeking stress, but the construct did not seem to be found in other countries. To examine whether if the variable of employment stress is a culture-bound concept and if the levels of stress experienced differ according to culture, we examined a total of 82 full-time undergraduate students, many with international background, at University of Utah Asia Campus. Multiple regression analyses were used to examine the relationships between international experience, employment stress, household income, and social and health-risk behaviors. The results showed that while household income predicted increased employment stress and employment stress predicted negative relationship with sociality, international experience did not predict increased employment stress, nor did the employment stress predict increased health-risk behaviors.
Keywords: Stress, Household Income, Sociability, Health-risk Behaviors